2002
DOI: 10.1128/mcb.22.4.1016-1026.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Insulin-Induced Degradation of Insulin Receptor Substrate 1

Abstract: Insulin receptor substrate 1 (IRS-1) plays an important role in the insulin signaling cascade. In vitro and in vivo studies from many investigators have suggested that lowering of IRS-1 cellular levels may be a mechanism of disordered insulin action (so-called insulin resistance). We previously reported that the protein levels of IRS-1 were selectively regulated by a proteasome degradation pathway in CHO/IR/IRS-1 cells and 3T3-L1 adipocytes during prolonged insulin exposure, whereas IRS-2 was unaffected. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 91 publications
(157 reference statements)
9
145
1
3
Order By: Relevance
“…Simultaneously, we observed an increase in the mobility of IRS-2, reflecting the loss of phosphorylation by S6K (32). As expected, over time the total levels of IRS-2 protein increased due to a decrease in proteasomal degradation that is normally promoted by S6K-mediated phosphorylation (33,34). As a direct readout of PI3K activity, we monitored phosphorylation of p85 on Tyr-458, a site that has previously been reported to track with the activation of this enzyme (35,36): rapamycin treatment resulted in an ϳ2.5-fold increase in phosphorylation on Tyr-458 within 16 h (Fig.…”
Section: Activation Of Pi3k In Cells Lacking Mtorc2supporting
confidence: 48%
“…Simultaneously, we observed an increase in the mobility of IRS-2, reflecting the loss of phosphorylation by S6K (32). As expected, over time the total levels of IRS-2 protein increased due to a decrease in proteasomal degradation that is normally promoted by S6K-mediated phosphorylation (33,34). As a direct readout of PI3K activity, we monitored phosphorylation of p85 on Tyr-458, a site that has previously been reported to track with the activation of this enzyme (35,36): rapamycin treatment resulted in an ϳ2.5-fold increase in phosphorylation on Tyr-458 within 16 h (Fig.…”
Section: Activation Of Pi3k In Cells Lacking Mtorc2supporting
confidence: 48%
“…Activation of PI3-kinase has been shown to be required for the growth factor-dependent ubiquitination and degradation of other proteins, e.g. the cytosolic adaptor protein IRS-1 (43,44) or forkhead transcription factors (34,45). Reelin-induced Dab1 degradation did not depend on PI3-kinase activation, however (Fig.…”
Section: Fig 1 Reelin Regulates the Protein Levels Of Dab1 In Neuronsmentioning
confidence: 78%
“…Effects of proteasome and protease inhibitors on degradation of IRS-1 by RA in breast cancer cells Previous studies have reported that the levels of IRS-1 can be regulated by IGF-I and insulin at the protein level via the ubiquitin-proteasome pathway (Sun et al, 1999;Lee et al, 2000;Zhang et al, 2000;Zhande et al, 2002). We therefore tested whether the effects of RA on IRS-1 were mediated via a similar mechanism.…”
Section: Ra Induces a Post-translational Modification Of Irs-1 In Mcfmentioning
confidence: 97%